Altered Effective Brain Connectivity During Habituation in First Episode Schizophrenia With Auditory Verbal Hallucinations: A Dichotic Listening EEG Study - Zheng, Leilei; Yan, Weizheng; Yu, Linzhen; Gao, Bin; Yu, Shaohua; Chen, Lili; Hao, Xiaoyi; Liu, Han; Lin, Zheng (Frontiers in Psychiatry, 2022)
Background: Habituation is considered to have protective and filtering mechanisms. The present study is aim to find the casual relationship and mechanisms of excitatory-inhibitory (E/I) dysfunctions in schizophrenia via habituation. Methods: A dichotic listening paradigm was performed with simultaneous EEG recording on 22 schizophrenia patients and 22 gender- and age-matched healthy controls. Source reconstruction and dynamic causal modelling (DCM) analysis were performed to estimate the effective connectivity and casual relationship between frontal and temporal regions before and after habituation. Results: The schizophrenia patients expressed later habituation onset (p<0.01) and hyper-activity in both lateral frontal-temporal cortices than controls (p=0.001). The patients also showed decreased top-down and bottom-up connectivity in bilateral frontal-temporal regions (p<0.01). The contralateral frontal-frontal and temporal-temporal connectivity showed a left to right decreasing (p < 0.01) and right to left strengthening (p < 0.01). Conclusions: The results give causal evidence for E/I imbalance in schizophrenia during dichotic auditory processing. The altered effective connectivity in frontal-temporal circuit could represent the trait bio-marker of schizophrenia with auditory hallucinations.